2000
DOI: 10.1091/mbc.11.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Induces Redox Reaction–mediated Dimerization and Superactivation of Oncogenic Ret Tyrosine Kinases

Abstract: The c-RET proto-oncogene encodes a receptor-type tyrosine kinase, and its mutations in the germ line are responsible for the inheritance of multiple endocrine neoplasia type 2A (MEN2A) and 2B (MEN2B). Ret kinases are constitutively activated as a result of MEN2A mutations (Ret-MEN2A) or MEN2B mutations (Ret-MEN2B). Here we demonstrate that UV light (UV) irradiation induces superactivation of the constitutively activated Ret-MEN2A and Ret-MEN2B as well as activation of c-Ret. Before UV irradiation, small percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…In order to assay if the soluble GFRa4 also has the capacity to activate RET, we added the sGFRa4-concentrate to naive Neuro 2a cells and immunoprecipitated RET from the lysates of these samples. The myelin basic protein has previously been reported to function as an exogenous substrate in in vitro kinase assays with kinase activated RET (Asai et al, 1995;Kato et al, 2000). The result of our in vitro kinase assay (Figure 2d) is in line with our co-immunoprecipitation results, and shows that soluble GFRa4 activates RET both in the absence and presence of PSPN.…”
supporting
confidence: 90%
“…In order to assay if the soluble GFRa4 also has the capacity to activate RET, we added the sGFRa4-concentrate to naive Neuro 2a cells and immunoprecipitated RET from the lysates of these samples. The myelin basic protein has previously been reported to function as an exogenous substrate in in vitro kinase assays with kinase activated RET (Asai et al, 1995;Kato et al, 2000). The result of our in vitro kinase assay (Figure 2d) is in line with our co-immunoprecipitation results, and shows that soluble GFRa4 activates RET both in the absence and presence of PSPN.…”
supporting
confidence: 90%
“…After the membranes had been reacted with the anti-Ret (reactive to both c-Ret and RFP-RET; Immuno-Biological laboratories, Gunma, Japan) antibody, the reaction was examined using Western Blot Chemiluminescence Reagent (DuPont NEN, Boston, MA, USA). Immunoprecipitation and immunohistochemistry with antiRet antibody (Kato et al, 1999(Kato et al, , 2000 or anti-S-100 protein (Iwamoto et al, 1991) were performed as described previously.…”
Section: Immunoblot Immunoprecipitation and Immunohistochemistrymentioning
confidence: 99%
“…Pourmahram et al (2008) provides an example of such an opportunity, as the authors detected a shift in sub-cellular localisation in PKCα in intrapulmonary arteries upon exposure to low concentrations of H 2 O 2 . Similarly, Kato (2000) and colleagues" discovery of redox-sensitive cysteine residues in c-Ret which are conserved across a range of kinases should prompt investigation of the redox-sensitivity of those kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Close investigation of the redox-regulation of proto-oncogenic RTK c-Ret by Kato et al(2000) has revealed that oxidative activation of the kinase occurs via disulfide bond formation between cysteine residues on two different c-Ret molecules, resulting in dimerisation. The cysteine residue in question, Cys376, is necessary for the basal activity of the kinase, as well as its up-regulation in response to UV irradiation.…”
Section: Rtks Such As the Insulin Receptor (Ir) Epidermal Growth Facmentioning
confidence: 99%